Deciphering elastoplastic properties from atomistic structure: Reactive coarse-grained MD for epoxies - Ries, Maximilian; Tiefenthäler, Jonas; Losert, Maximilian; Possart, Gunnar (International Journal of Adhesion and Adhesives, 2026)
Adhesive joints provide a better strength-to-weight ratio than traditional fastening methods and thus play a vital role in lightweight and cost-efficient engineering designs. The interaction of adherend and adhesive causes a region with different local resin-to-hardener ratios, e.g., due to demixing or sterically hindered diffusion during curing. Consequently, this interphase exhibits a mechanical behavior that differs from that of the bulk adhesive, immediately implying thickness-dependent properties of the joint, which should be, but are not yet, addressed in engineering. Additionally, these local gradients of structural and especially mechanical properties are, if at all, very difficult to assess by experimental methods. As a remedy, we derive the elastoplastic material parameters for bulk adhesives covering a wide range of mixing ratios. To this end, we simulate the curing and deformation of pure epoxy with reactive, coarse-grained molecular dynamics (CGMD) and introduce an extrapolation scheme to obtain the quasi-static material response. The latter removes the viscous contributions, which facilitates the comparison of ultra-fast MD with conventional mechanical testing. Based on these results, we calibrate elastoplastic constitutive models with VOCE-type hardening and obtain mixing ratio-dependent Young's modulus, Poisson's ratio, yield stress, and hardening parameters. Finally, we obtain the correlation between these material parameters and structural characteristics, such as density and curing degree, for a wide range of mixing ratios. With these results, we can then conclude on the local mechanical properties of interphases, based on CGMD simulations of the curing of adhesive joints, which inherently provide the local structure gradients in the vicinity of the adherends [1].
CRIS-Team Scopus Importer:2025-11-21
Keywords: Constitutive modeling; Epoxy; Molecular dynamics; Resin-hardener ratio; Structure–property relation